Integrasi Metode Pembelajaran Pendidikan Islam Anak Usia Dini dan Pendidikan Agama Islam untuk Meningkatkan Perkembangan Sosial Emosional Anak - Gulo, Ismail Kabir; Ridha, Nikmatur (AUD Cendekia: Journal of Islamic Early Childhood Education, 2025)
This study aims to describe the integration of PIAUD (Early Childhood Islamic Education) and PAI (Islamic Religious Education) learning methods at RA Muslimat Humene and analyze their impact on children's social-emotional development. This study uses a qualitative approach with a case study method that observes daily learning practices at the institution. The results show that the integration of academic learning and Islamic values is carried out through habituation, Islamic value-based games, and routine worship activities, which have succeeded in improving children's empathy, emotional regulation, and social skills. However, this study also identifies challenges faced by teachers, such as limited religious pedagogical competence, a lack of integrative modules, and difficulties in managing classes that require a flexible approach. These findings contribute theoretically to the development of Islamic early childhood education curricula and provide practical recommendations for educators and institution managers to improve the integration of Islamic character education in early childhood education.